2009
DOI: 10.1111/j.1601-5223.1975.tb01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of a homoeotic gene in Drosophila melanogaster

Abstract: Polycomb (Pc, Pc2) — one of three closely linked nonallelic homoeotic mutants in chromosome 3 of Drosophila melanogaster that change the development of the hind legs to that of the first legs — is located in the left arm of the chromosome between ri and eg. By using a duplication of the salivary chromosome segment 75A–B through 80, flies were obtained that had two or three doses of Pc alleles. Evidence is given to show that Pc2 and Pc+ are antagonistic in their actions indicating an active competition between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The first Polycomb phenotype was described in 1947 by Pamela Lewis as an x-rayinduced Drosophila mutant displaying an abnormal number of sex combs and an Antennapedia-like phenotype of antenna-to-leg transformation (12). Thirty years later, the first Polycomb gene (Pc) locus was mapped (13), and the connection between Pc and repressive activity on the Bithorax complex (BX-C) locus was realized (14). The antagonistic roles of PcG in transcriptional repression and TrxG in transcriptional activation of homeotic genes in Drosophila led to the paradigm of the tight regulation of transcription by PcG and TrxG for the spatiotemporal control of developmental genes (8,15).…”
Section: Trithorax and Polycomb Groups Of Proteinsmentioning
confidence: 99%
“…The first Polycomb phenotype was described in 1947 by Pamela Lewis as an x-rayinduced Drosophila mutant displaying an abnormal number of sex combs and an Antennapedia-like phenotype of antenna-to-leg transformation (12). Thirty years later, the first Polycomb gene (Pc) locus was mapped (13), and the connection between Pc and repressive activity on the Bithorax complex (BX-C) locus was realized (14). The antagonistic roles of PcG in transcriptional repression and TrxG in transcriptional activation of homeotic genes in Drosophila led to the paradigm of the tight regulation of transcription by PcG and TrxG for the spatiotemporal control of developmental genes (8,15).…”
Section: Trithorax and Polycomb Groups Of Proteinsmentioning
confidence: 99%
“…Adapted from Carroll (Carroll, 1995). REVIEW Development 140 (19) from earlier segmentation genes (Irish et al, 1989); a cellular memory system based on the action of Polycomb (PcG)/trithorax (trxG) group proteins (Denell, 1978;Puro and Nygrén, 1975;Wedeen et al, 1986); and cross-regulatory interactions among the Hox genes themselves (Morata and Kerridge, 1982;Struhl, 1982). Regarding the latter mechanism, it was observed that the more posterior Hox genes are able to repress the expression (and suppress the function) of more anterior genes, a process termed 'posterior prevalence' (Akam, 1987;Duboule and Morata, 1994;Hafen et al, 1984;Harding et al, 1985).…”
Section: Hox Transcriptional Regulation In Space and Timementioning
confidence: 99%
“…In the meso-and metathorax of mutant individuals, on the other hand, the level of repression would be reduced because of the competition between wild type and antimorphic mutant gene products for the limited number of "effector" molecules. Analogously with the hypothesis of PURO and NYGREN (1975) for Polycomb, it could be proposed that the Notch gene is a regulator gene which in the wild type activates the function of "bristle genes" and "wing vein genes" with a limited amount of effectors (coinductors) also being involved. In the presence of antimorphic mutant gene products in Ax' heterozygotes there would be a competition between the wild type and mutant gene products for the coinductor molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally known that the products of regulator genes in bacterial system are activated or inactivated by special small effector molecules such as lactose in the lactose operon system. On the basis of gene dosage studies PURO and NYGREN (1975) concluded that the mutation Polycomb-2 ( P c 2 , 3-47. I ) in Drosophila mrlunogaster is antimorphic.…”
Section: Discussionmentioning
confidence: 99%